Hypostomus velhochico, a new keeled Hypostomus Lacépède, 1803 (Siluriformes: Loricariidae) from the rio São Francisco basin in Brazil - Zawadzki, Cláudio H.; Oyakawa, Osvaldo T.; Britski, Heraldo A. (Zootaxa, 2017)
Hypostomus velhochico sp. n., is described from the rio São Francisco basin, in the states of Minas Gerais and Bahia, Brazil. The new species is mainly distinguished from its congeners by a combination of characters such as slender bicuspid teeth, dentaries angled more than 90 degrees, conspicuous keels along lateral series of plates, small roundish dark spots, one plate bordering supraoccipital, spots aligned along lateral series of plates, and by attaining small to medium size. Hypostomus velhochico is widespread in the rio São Francisco basin and has a more similar general pattern of external morphology to species from the Northeastern Brazilian Coastal drainages than to species of the rio São Francisco basin. Aspects about its ecology and its putative relationship are discussed.